From Boston to Chinese parallel to deferred acceptance: Theory and experiments on a family of school choice mechanisms - Yan Chen; Kesten Onur (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
We characterize a parametric family of application-rejection school choice mechanisms, including the Boston and Deferred Acceptance mechanisms as special cases, and spanning the parallel mechanisms for Chinese college admissions, the largest centralized matching in the world. Moving from one extreme member to the other results in systematic changes in manipulability, stability and welfare properties. Neither the ex-post dominance of the DA over the equilibria of Boston, nor the ex-ante dominance of Boston equilibria over the DA in stylized settings extends to the parallel mechanisms. In the laboratory, participants are most likely to reveal their preferences truthfully under the DA mechanism, followed by the Chinese parallel and then the Boston mechanisms. Furthermore, while the DA is significantly more stable than the Chinese parallel mechanism, which is more stable than Boston, efficiency comparisons vary across environments.
Keywords: C78; C92; D82; 330; school choice; Boston mechanism; Chinese parallel mechanism; deferred acceptance; experiment